Visible Luminescence of the InGaN/GaN Ultraviolet Light-emitting Diodes 365 nm - V.P.В Veleschuk; A.I.В Vlasenko; Z.K.В Vlasenko; D.N.В KhmilвЂ™; O.M.В Kamuz; I.V.В Petrenko; V.P.В Tartachnyk; A.V. Shulga; V.V.В Borshch (Журнал нано- та електронної фізики)
Visible electro- and photoluminescence of the ultraviolet LEDs (пЃ¬В пЂЅВ 365В nm) was studied. It is established that at nitrogen temperature yellow electroluminescence is absent and occurs when the current or temperature increases. The light output power and luminous efficiency of the yellow electroluminescence in the 450-740В nm range were measured. At temperature decreasing an increase of the luminescence intensity in the spectrum range 393-460вЂ¦490В nm is observed.